Zürich cementless total hip arthroplasty as a treatment option for capital physeal fractures in dogs: Outcome in 53 cases. Issue 5 (12th March 2021) - Alvarez‐Sanchez, Alejandro; Amsellem, Pierre; Vezzoni, Luca; Vezzoni, Aldo
Abstract: Objective: To review the outcome of dogs that underwent Zürich cementless total hip arthroplasty (Z‐THA) for the repair of acute and chronic capital physeal fractures (CPF) and document the CPF‐related hip remodeling. Study design: Retrospective study. Sample population: Fifty‐three Z‐THA in 53 dogs. Methods: Medical records of dogs (2006‐2019) that underwent Z‐THA for CPF management were reviewed. Dogs were divided into two groups on the basis of the days elapsed between CPF diagnosis and Z‐THA, acute (≤30 days) and chronic (>30 days). Hip remodeling variables were determined from preoperative radiographs or intraoperatively. Descriptive statistics were performed, and the complication rates, outcome, and coxofemoral remodeling were recorded. Comparisons of remodeling variables and rates between groups were performed by using Fisher's exact test. Results: In total, 23 of 53 (43.4%) cases were acute, and 30 of 53 (56.6%) cases were chronic. There was no difference in the femoral remodeling rates between the acute and chronic groups ( P = .184), whereas acetabular remodeling was more prevalent in the chronic group ( P < .001). Intraoperative complications occurred in four of 53 (7.5% [1/23 acute, 3/30 chronic]) cases, and postoperative complications occurred in six of 53 (11.3% [2/23 acute, 4/30 chronic]) cases. Good clinical outcomes were achieved in 51 of 53 (96.2% [21 acute, 30 chronic]) cases. Conclusion: Complication rates of Z‐THA for CPF repair were similar to the complication rates reported for Z‐THA of dysplastic hips. Hip remodeling was common regardless of CPF chronicity. Clinical significance: Zürich cementless total hip arthroplasty is viable for surgical management of CPF. There is a high likelihood that hip remodeling will be encountered, even in fractures treated within 30 days of presenting for hind limb lameness.